In praise of poverty : Hannah More counters Thomas Paine and the radical threat - Scheuermann, Mona (The University Press of Kentucky, 2015)
In her own time and in ours, Hannah More (1745-1833) has been seen as a benefactress of the poor, writing and working selflessly to their benefit. Mona Scheuermann argues, however, that More's agenda was not simply to help the poor but to control them, for the upper classes in late eighteenth-century England were terrified that the poor would rise in revolt against Church and King. As much social history as literary study, In Praise of Poverty shows that More's writing to the poor specifically is intended to counter the perceived rabble rousing of Thomas Paine and other radicals active in the.